Digital avionics handbook - Spitzer, Cary R.; Ferrell, Uma; Ferrell, Thomas (CRC Press, 2015)
] Digital Avionics Handbook offers a comprehensive view of avionics. Complete with case studies of avionics architectures as well as examples of modern systems flying on current military and civil aircraft, this Third Edition includes: Ten brand-new chapters covering new topics and emerging trends, significant restructuring to deliver a more coherent and cohesive story, and updates to all existing chapters to reflect the latest software and technologies. Featuring discussions of new data bus and display concepts involving retina scanning, speech interaction, and synthetic vision, the Digital Avionics Handbook, Third Edition provides practicing and aspiring electrical, aerospace, avionics, and control systems engineers with a pragmatic look at the present state of the art of avionics